Observed Vertical Structure of Convection During Dry and Wet Summer Monsoon Epochs Over the Western Ghats. Issue 3 (7th February 2019) - Utsav, Bhowmik; Deshpande, Sachin M.; Das, Subrata K.; Pandithurai, Govindan; Niyogi, Dev
Abstract: Summer precipitation over the Western Ghats is an important facet of Indian monsoon. The vertical structure of mesoscale convection during dry and wet epochs of regional precipitation is studied using X‐band Doppler radar, for the first time. The observed characteristics are distinctly different in terms of small‐scale convective and large‐scale atmospheric features for the dry versus wet regimes. The depth and intensity of convection is analyzed using various echo‐top heights (ETHs). The frequency distribution of 0‐ and 15‐dBZ ETH exhibits bimodality during the dry period, which changes to unimodal in wet period. Top heights of precipitating convection (characterized by 30‐dBZ echoes) decreased with low‐level static stability, suggesting preponderance of shallow convection with little stratiform clouds. Suppressed heating in the dry period is a signature of reduced 0‐dBZ ETH occurrence. However, its enhanced occurrence during the wet period resulted in cooling below 2 km and increased heating aloft with maxima at 6 km. Near high precipitation events, midtropospheric humidity rapidly builds up over 2–3 days prior to increase in cloud‐top heights and areal coverage. Observations indicate large amplitude of ETH diurnal cycle during the dry period (especially over leeside) accompanied by weak upstream winds. However, during the wet period, smaller amplitude of ETH is evident (throughout the radar domain) under strong upstream wind conditions. Convective activity during the late afternoon hours produces higher lighting flashes in the dry period compared to the wet. The lightning occurrences are related with penetrations of 30‐dBZ ETH above the freezing level and convective area fractions. Key Points: Dry and wet period convection characteristics are observed to be different in terms of their small‐scale convective and large‐scale features Positive feedback between low‐level heating and static stability maintains the shallow nature of convection over the Western Ghats Large (small) amplitude of convection diurnal cycle is observed during the dry (wet) period with weak (strong) cross‐shore upstream winds